ASPEK HUKUM CYBERBULLYING DI KALANGAN REMAJA DALAM PERSPEKTIF UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Hidayah, Astika Nurul; Kartini, Ika Ariani; Susanti, Rahtami (Universitas Muhammadiyah Tangerang, 2021)
The world of today's youth cannot be separated from the internet. In addition to using the internet for learning needs, teenagers also use the internet to interact in cyberspace through social media. Although it provides many benefits, social media in cyberspace also has the potential to cause negative impacts in the form of cyberbullying, namely mental violence by a person or group of people against another person or group of people in cyberspace so that the victim feels mistreated. According to Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE), cyberbullying is categorized as a crime and has legal sanctions. The purpose of the science and technology activity for the community